Barriers to generic antiseizure medication use: Results of a global survey by the International League Against Epilepsy Generic Substitution Task Force. Issue 2 (18th February 2022) - Niyongere, Jenna; Welty, Timothy E.; Bell, Michelle W.; Consalvo, Damian; Hammond, Charles; Leung, Howan; Patsalos, Philip N.; Ryan, Melody; Suansanae, Thanarat; Zhou, Dong; Zuellig, Hazel
Abstract: The objective of this study was to identify and quantify barriers to generic substitution of antiseizure medications (ASM). A questionnaire on generic ASM substitution was developed by the International League Against Epilepsy (ILAE) Task Force on Generic Substitution. Questions addressed understanding of bioequivalence, standards for generic products, experiences with substitution, and demographic data. The survey was web‐based and distributed to ILAE chapters, their membership, and professional colleagues of task force members. Comparisons in responses were between ILAE regions and country income classification. A total of 800 individuals responded, with 44.2% being from the Asia‐Oceania ILAE Region and 38.6% from European Region. The majority of respondents had little or no education in generic substitution or bioequivalence. Many respondents indicated lack of understanding aspects of generic substitution. Common barriers to generic substitution included limited access, poor or inconsistent quality, too expensive, or lack of regulatory control. Increase in seizures was the most common reported adverse outcome of substitution. Of medications on the World Health Organization Essential Medication list, problems with generic products were most frequent with carbamazepine, lamotrigine, and valproic acid. Several barriers with generic substitution of ASM revolved around mistrust of regulatory control and quality of generic ASM. Lack of education on generic substitution is also a concern. Generic ASM products may be the only option in some parts of the world and efforts should address these issues. Efforts to address these barriers should improve access to medications in all parts of the world.